Unique organization of Leptospira interrogans rRNA genes. - Fukunaga, M (1989)
We cloned Sau3AI fragments containing the rRNA genes for Leptospira interrogans serovar canicola strain Moulton in the BamHI site of lambda EMBL3 bacteriophage DNA. Physical maps of the fragments were constructed, and the locations of the rRNA genes were determined by Southern blot hybridization and S1 protection. Each fragment of the 23S or the 16S rRNA gene contained at least one copy of the 23S or the 16S sequence. Genomic hybridization showed that there were two genes for the 23S rRNA and the 16S rRNA but only one gene for the 5S rRNA on the chromosome of L. interrogans. The results revealed the important fact that each rRNA gene is located far from the other rRNA genes. Our findings, accordingly, also suggest that these rRNA genes are expressed independently in this organism.